Demand against Law and Using Authority in Corruption Criminal Action - Indra Gunawan; Alvi Syahrin (Budapest International Research and Critics University, 2019)
Acts against the law and Abuse of authority in criminal acts of corruption are regulated in Article 2 and Article 3 law No. 31 1999 as amended to law No. 20 tahun 2001 concerning Eradication of Corruption (UUPTPK). There is a fundamental difference between the two acts, although these two actions are elements that determine whether or not an action can be declared a criminal act, furthermore the two acts are also important to determine whether someone can be blamed for corruption or not. Both actions (against the law and abuse of authority) are important to distinguish the boundaries of corruption and are also interesting to talk about. Especially then if it is associated with the subject of criminal acts of Corruption, namely: Person (naturleijk person) and Corporation (recht person). This means that whether the two acts are against the law and abuse of authority can be done by both legal subjects.